2020
DOI: 10.47836/pjtas.43.4.19
|View full text |Cite
|
Sign up to set email alerts
|

A Report on Introduced Amazon Sailfin Catfish, Pterygoplichthys pardalis in Gombak Basin, Selangor, with Notes on Two Body Patterns of the Species

Abstract: Invasive introduced fish species are well known for their deleterious impacts on aquatic biodiversity and environment. This study provides the first report on the occurrence of introduced Amazon sailfin catfish, Pterygoplichthys pardalis from the Gombak basin, Selangor, Malaysia, where the suckermouth catfish, Hypostomus plecostomus and vermiculated sailfin catfish, Pterygoplichthys disjunctivus had been previously reported. Besides, selected morphometric and meristic measurements between P. pardalis and P. di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In this study, the presence of P. disjunctivus 'type B'. The same finding has been reported by Saba et al (2020), with the presence of the new body pattern of Pterygoplichthys pardalis 'type B' in Pusu River, Gombak basin Malaysia [10]. The presence of the new body pattern type could be resulted from the hybridization of P. pardalis and P.disjunctivus, or could it be another variation of these two species.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, the presence of P. disjunctivus 'type B'. The same finding has been reported by Saba et al (2020), with the presence of the new body pattern of Pterygoplichthys pardalis 'type B' in Pusu River, Gombak basin Malaysia [10]. The presence of the new body pattern type could be resulted from the hybridization of P. pardalis and P.disjunctivus, or could it be another variation of these two species.…”
Section: Resultssupporting
confidence: 82%
“…In several research papers, two species of Pterygoplichthys were reported found in Malaysia. The populations of P. pardalis were found in Langat river, Selangor, Perak river, Perak [8], Muar river, Negeri Sembilan [4], Gombak river, Selangor [9] and population were established in Pusu river, Selangor where at least two species of Pterygoplichthys thrive well: Pterygoplichthys pardalis and P.disjunctivus [10].…”
Section: Resultsmentioning
confidence: 99%
“…The sailfin catfish species is one of the alien species living in Tempe Lake in South Sulawesi, Indonesia (Febrianti et al 2019). Sailfin catfish is considered invasive species that compete with native species for both food and habitat (Saba et al 2020). The sailfin catfish has come to dominate the fish population in the lake; in addition to ecosystem impacts, there has been a significant reduction in the populations of other (native) fish species, some of which are no longer found (Chaicana and Jongphadungkiet 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The sailfin catfish has come to dominate the fish population in the lake; in addition to ecosystem impacts, there has been a significant reduction in the populations of other (native) fish species, some of which are no longer found (Chaicana and Jongphadungkiet 2012). This situation has also resulted in a decrease in the income and welfare of local fishers in Tempe Lake, as 70% of the catch is dominated by sailfin catfish (Saba et al 2020). Sailfin catfish have become dominant because, unlike most other fish species in the lake, they are not exploited either by commercial fisheries or for subsistence as a source of nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, alien fishes such as tilapia ( Oreochromis sp. ), sailfin catfishes ( Pterygoplichthys pardalis and Pterygoplichthys disjunctivus ), and guppy ( Poecilia reticulata ) have been reportedly introduced both intentionally and inadvertently for different purposes [ 3 , 25 , 26 ]. Therefore, alien fishes are present and, in some cases, have established breeding populations in the inland waters of this country [ 27 ].…”
Section: Introductionmentioning
confidence: 99%